2017
DOI: 10.1155/2017/2938691
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Dental Follicle Width and Maxillary Impacted Canines’ Descriptive and Resorptive Features Using Cone-Beam Computed Tomography

Abstract: Objectives To assess the relationship between dental follicle width and maxillary impacted canines' descriptive and resorptive features with three-dimensional (3D) cone-beam computed tomography (CBCT). Methods The study comprised 102 patients with cone-beam computed tomography 3D images and a total of 140 impacted canines. The association between maxillary impacted canine dental follicle width and the variables of gender, impaction side (right and left), localization of impacted canine (buccal, central, and pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 20 publications
(17 reference statements)
1
17
0
3
Order By: Relevance
“…Tooth eruption is the vertical movement from the intra-alveolar non-functional position to the functional line of occlusion [1]. The maxillary canine erupts at age 11 in boys and at approximately 10.6 years in girls [2], with a longer development period, deeper area of formation, and a more difficult path to the occlusal position [3][4][5][6]. Coulter and Richardson observed a distance traveled from formation to eruption of 22 mm [7].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Tooth eruption is the vertical movement from the intra-alveolar non-functional position to the functional line of occlusion [1]. The maxillary canine erupts at age 11 in boys and at approximately 10.6 years in girls [2], with a longer development period, deeper area of formation, and a more difficult path to the occlusal position [3][4][5][6]. Coulter and Richardson observed a distance traveled from formation to eruption of 22 mm [7].…”
Section: Introductionmentioning
confidence: 99%
“…It is considered impacted when it is completely or partially covered by mucoperiosteum and bone, distant from the place and time that corresponds to it in the mouth [8,9]. After the third molar, the canine is the tooth that most frequently presents anomalies in its eruption [5,9,10], with a prevalence of 1-3% [2,[4][5][6][11][12][13][14][15], and in the majority of the cases, it is an asymptomatic process [14]. Exclusively within orthodontic practice, the prevalence amounts to 23.5% of orthodontic patients [2,16].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Regarding the size of canine dental follicle, no significant correlation was found between follicle width and the variables gender, impaction side, and MIC location. It could not be confirmed that increased dental follicle width of the MICs exhibited more resorption risk for the adjacent lateral incisors (30). A Brazilian study (28) concluded that a wide dental follicle of impacted canines was not associated with a higher incidence of external root resorption of adjacent teeth .…”
Section: Cbct Assessment Of Incisor Root Resorption Location (Tab Iii)mentioning
confidence: 90%